Peran Self-Esteem terhadap Relationship Flourishing melalui AIM (Attention, Interpretation and Memory) dan Positivity pada Individu yang menikah - O. Irene Prameswari Edwina; Cindy Maria Setyana; Tessalonika Sembiring (Humanitas (Jurnal Psikologi), 2022)
Relationship flourishing demonstrates the existence of meaningful connectedness and activities that aim to help couples grow as individuals and couples. When individuals are happy and able to carry out their roles functionally, this will have a positive impact on the mental health of each family member (Fower, 2016). This study aims to examines whether there is a mechanism for the role of self-esteem on relationship flourishing in husband/wife with AIM and positivity factors as mediators. Data were collected through self-esteem, AIM, positivity and relationship flourishing questionnaires using google form. There are 252 husbands and wives who are participated in this study. Data analysis uses Model 4 of SPSS PROCESS (Hayes, 2018). The results show that self-esteem does not play a direct role in relationship flourishing and only positive emotions act as a mediator between self-esteem and relationship flourishing in husband/wife. Suggestions are discussed further in this study.